(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The main objective of this thesis is to study various methods used for rehabilitation repairs and retrofitting in construction industry that includes new construction techniques and traditional construction techniques, to minimize retrofitting costs and waste without affecting production quality and to minimize environmental effects.This study includes visual inspection and advance technique to rehabilitation repairs and retrofitting survey in which we can find out the factor affecting the repair cost which directly related with material use in retrofitting. The factors affecting the retrofitting cost and time were identified through the literature based on previous research. The comparison of time for both material used in retrofitting work in each material showed that the material which includes advanced method, new techniques, installation process is the most suitable alternative to the existing traditional method like cement slurry.